Incidence of cancer in chronic inflammatory demyelinating polyneuropathy: a nationwide cohort study in South Korea - Choi, Kyomin; Jung, Sohee; Jung, Gucheol; Kim, Dayoung; Oh, Jeeyoung (Frontiers in Neurology, 2024)
Background: Chronic inflammatory demyelinating polyneuropathy (CIDP) is a rare disease, and the potential risk of cancer in patients with CIDP remains an important concern during treatment. However, a comprehensive epidemiological study examining this association is yet to be conducted. This study aimed to investigate the incidence of cancer in patients with CIDP in South Korea using data from the Korean Health Insurance Review and Assessment Service (HIRA) database.Methods: Data from the HIRA database between January 2016 and June 2021 were analyzed. The actual incidence of cancer in patients with CIDP was compared with the expected incidence based on the general population statistics in South Korea, with adjustments for age.In total, 888 patients with CIDP were included in the analysis, of whom 50 (5.63% of malignancy incidence) were newly diagnosed with cancer during the study period. Among the patients with CIDP diagnosed with cancer, 32 (64.00%) were aged 60 years or older, and 36 (72.00%) were male. The observed number of cancer diagnoses corresponded to an incidence rate of 5.63%, with a standardized incidence ratio (SIR) of 2.83 (95% confidence interval [CI]: 1.89-4.39) compared to the expected cancer incidence rate of 2.00%. Notably, the SIR for malignancies of lymphoid, hematopoietic, and related tissues, excluding malignant immunoproliferative diseases, multiple myeloma, and plasma cell neoplasms (C81-96, except C88 and C90), was the highest at 8.51 (95% CI: 4.18-19.83).Our study shows a potential association between CIDP and an increased risk of hematological malignancies, which is consistent with previous investigations. Further studies are required to better understand the relationship between CIDP and cancer.